The Effect of Marmet Technique on Mother’s Satisfaction in Breastfeeding - Rani Dwi Sulistiawati1, Tiyas Kusumaningrum1, Retnayu Pradanie1, Ni Ketut Alit Armini1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The Marmet technique is a safe way to stimulate the breast to produce more milk. The administration of Marmet techniques to mothers who produced little to no amount of breast milk showed good results. Palms and fingers are recommended for breast milk milking due to them being practical, effective and efficient. Purpose: To determine the effect of Marmet technique on maternal satisfaction in breastfeeding. Method: This research applied quasi experiment design. There were 40 respondents, each consisting of a treatment group and a control group that met the inclusion criteria. Data were collected using questionnaires and observation sheet. The data were then analyzed using Mann Whitney and Wilcoxon’s Test (? <0.05). Results: Statistical test results ofWilcoxon Signed Rank Test in the treatment group with the value of sig (2-tailed) obtained p = 0.000 in which p <0.05 indicates that there is a significant effect of Marmet technique on maternal satisfaction in breastfeeding. However, the control group obtained p = 0.083 in which p> ?>0.05, meaning that there is no significant effect of Marmet technique on maternal satisfaction in breastfeeding. Conclusion: The satisfaction of the mother in breastfeeding has increased after being intervened with Marmet technique.